PALEOCENE-EOCENE BOUNDARY EVENTS IN THE NORTHEASTERN PERI-TETHYS - Gavrilov Y.O.; Shcherbinina E.A.; Oberhänsli H. (My University, 2003)
In the northeastern Peri-Tethys epicontinental basin stretching from the Black Sea to Tadjikistan, a sapropelitic bed with total organic carbon (TOC) contents up to 20% and enriched in redox-sensitive elements was deposited during the Initial Eocene Thermal Maximum (IETM), recognized by occurrence of negative carbon isotope excursion in organic carbon and carbonate. In the sapropelitic bed, calcareous plankton decreased in abundance, a bentic foraminiferal extinction occured, dinocysts were abundant, and there were abnormally thick-walled dinocysts and asimmetric calcareous nannoplankton species. We argue that the sapropelitic bed accumulated as a result of high productivity, triggered by an influx of nutrients that reached the basin when organic- and P-rich sediments in low-lying coastal areas were flooded during a rapid transgression. High productivity led to oxygen depletion, decimating benthic foraminiferal assemblages. Organic biomarkers suggest that at least in some places even waters in photic zone became anoxic. The dysoxia/anoxia might have been exacerbated by stratification, resulting from high runoff in the humid western region, high evaporation in the arid eastern area. Anoxia/dysoxia ended gradually. We suggest that deposition of large amount of organic matter in the northeastern Peri-Tethys may have been a factor in terminating the IETM.
Keywords: Eocene; Paleocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен